Evolution of diverse antiviral CD8+ T cell populations after murine cytomegalovirus infection. - Sierro, S; Rothkopf, R; Klenerman, P (2005)
Cytomegalovirus (CMV) is a major human pathogen normally controlled by cellular immune responses. The infection can be modeled in the mouse using murine CMV (MCMV). During the latent phase of infection, two different patterns of CD8(+) T cell responses have been observed: some specificities show increasing frequencies over time ("memory inflation"), while others, which are present acutely, are barely detectable at later time points. This distinction is independent of initial immunodominance. We analyzed the extent to which such responses differ functionally and tracked both their population distribution and their evolution over time. We observed two clear patterns of memory development that diverged early after infection. Acutely, CD8(+) T cells directed against all epitopes showed similar activation, phenotype and distribution. Thereafter, one set of responses ("inflationary") increased in frequency over time, was found in high numbers in non-lymphoid organs and was associated with an activated (CD28(low) CD27(low)CD122(low)) phenotype. In contrast, CD8(+) T cells responses specific for other MCMV epitopes ("non-inflationary") showed a slow reversion to a classical "central" memory phenotype without enrichment in non-lymphoid organs. A simple model to describe the equilibrium state in MCMV is presented, which may point to previously unexplored antiviral populations present after human CMV infection.